Urinary Erythrocyte-Derived miRNAs: Emerging Role in IgA Nephropathy - Zhi-Yu Duan; Guang-yan Cai; Ji-Jun Li; Ru Bu; Xiang-Mei Chen (Karger Publishers, 2017)
Hematuria is one of the basic clinical manifestations of IgA nephropathy (IgAN). Isolated microscopic hematuria or microscopic hematuria combined with proteinuria is risk factor for the long-term prognosis of IgAN. Current evidence of the consequences of glomerular hematuria rests on insights from basic research on the molecular mechanisms of hemoglobin and related reactive oxygen species-induced tubular injury as well as on the clinical evidence of macroscopic hematuria-associated acute kidney injury (AKI) in IgAN. These researches may simply elucidate some effects of macroscopic hematuria but not microscopic hematuria. Recent studies conducted on blood and urinary erythrocytes have made progress. Researches have revealed that mature erythrocytes contain abundant, long, non-coding RNA, miRNA (microRNA) and Y RNA. Among the top 50 expressions of erythrocyte-derived miRNAs, 33 (66%) of them may be the potential urinary biomarkers of IgAN. Moreover, when urinary erythrocytes are compressed while exiting out of an impaired nephron, erythrocyte-derived vesicles (including microvesicles and apoptotic vesicles) may increase. Animal models for hematuria and human biopsy tissues confirm renal parenchymal cells could phagocytose red blood cells and erythrocyte-derived vesicles. These vesicles, which contain miRNAs, may alter the transcriptome of recipient cells and impact the occurrence and development of IgAN.